Efficient antibacterial photocureable coating and preparation method thereof
By ultrasonic dispersing and chemically modifying the hydroxylated carbon nanotubes with silane coupling agent, silver-carrying modified carbon nanotubes are formed, and chemical bonds are formed with graphene oxide through epoxy ring-opening reaction to form a composite antibacterial agent, which solves the problem that conventional epoxy acrylate photocuring coatings do not have good antibacterial properties, and achieves the effect of significantly improving antibacterial properties and durability.
Patent Information
- Application Number
- CN202411843444.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-14
- Publication Date
- 2025-04-04
AI Technical Summary
The cured paint film formed by conventional epoxy acrylate photocuring coatings does not have good antibacterial properties. When graphene or carbon nanotubes are directly added, the effective performance of antibacterial properties is hindered due to the agglomeration between nanoparticles.
A composite antibacterial agent was prepared by ultrasonic dispersing and chemically modifying the hydroxylated carbon nanotubes with silane coupling agent to form silver-carrying modified carbon nanotubes, and reacting with graphene oxide through epoxy ring-opening reaction to form chemical bonds. The antibacterial agent is linked together by reducing graphene oxide and carbon nanotube macromolecular structures, combined with the antibacterial effect of silver nanoparticles, significantly improving the antibacterial properties of photocuring coatings.
It realizes the construction of a dense and complex antibacterial network in photocured coatings, significantly improves antibacterial performance, and avoids the easy migration and precipitation of antibacterial agents in the paint film, and significantly improves the antibacterial durability of the photocured paint film.
Smart Images

Figure BDA0005188461800000011 
Figure BDA0005188461800000041 
Figure BDA0005188461800000061
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of photocurable coatings, and in particular to a high-efficiency antibacterial photocurable coating and a preparation method thereof. Background Art
[0002] As an important type of UV curing material, epoxy acrylate light-curing coatings combine the properties of epoxy resin and acrylate to form a composite material with excellent performance and fast curing. Epoxy acrylate light-curing coatings are widely used in the field of wood coatings.
[0003] Epoxy acrylate can quickly form a three-dimensional network structure during the light curing process, which greatly shortens the curing time and improves production efficiency. The cured epoxy acrylate coating has the characteristics of high hardness, high gloss, excellent chemical resistance, good water resistance, hot water resistance and drug resistance. These properties make epoxy acrylate light curing coatings excellent in anti-corrosion protection in humid environments.
[0004] However, epoxy acrylate photocuring coatings generally do not have good antibacterial effects. Studies have shown that adding antibacterial agents such as graphene and carbon nanotubes to acrylate-based photocuring coating systems can improve the antibacterial properties of the resulting paint film. However, when graphene and carbon nanotubes are directly added to the coating system, graphene and carbon nanotube nanoparticles are easily agglomerated due to their small surface energy, which hinders the effective performance of antibacterial properties. In response to this problem, some studies have adopted a modification method to increase the spacing between adjacent nanoparticles to reduce the probability of agglomeration between nanoparticles, but the effect is limited. At present, there is no report on a composite antibacterial agent formed by compounding graphene and carbon nanotube nanoparticles through chemical bonds. Summary of the invention
[0005] The problem in the prior art is that the cured paint film formed by conventional epoxy acrylate photocuring paint does not have good antibacterial properties. In view of the above technical problems, the present invention provides a high-efficiency antibacterial photocuring paint, the formula of which is calculated by weight and includes the following components:
[0006]
[0007] Preferably, the epoxy acrylate includes one or a combination of two or more of Changxing UV epoxy oligomer 6210G, 621A80, 6215-100, 623A80, and 6233.
[0008] Preferably, the reactive diluent monomer includes one or a combination of two or more of propylene glycol diacrylate, trimethylolpropane triacrylate or isobornyl acrylate.
[0009] Preferably, the photoinitiator includes one of photoinitiator 184, photoinitiator 1173, photoinitiator TPO, photoinitiator 819, or a combination of two or more thereof.
[0010] Preferably, the method for preparing the antibacterial agent comprises the following steps:
[0011] (1) adding hydroxylated carbon nanotubes and a silane coupling agent to an ethanol aqueous solution with a mass concentration of 95%, ultrasonically dispersing for at least 2 hours, and then isothermally reacting at 60° C. for at least 6 hours. After the reaction is completed, filtering to obtain a solid product, washing with acetone at least 3 times, and then vacuum drying at 80° C. for at least 12 hours to obtain modified carbon nanotubes, wherein the mass ratio of the hydroxylated carbon nanotubes to the silane coupling agent is 1:1, and the silane coupling agent is composed of KH560 and KH570 in a mass ratio of 1-3:1-3; the mass concentration of the hydroxylated carbon nanotubes in the ethanol aqueous solution is 20-25 g / L;
[0012] (2) adding the silver nitrate dispersion to the modified carbon nanotube dispersion to obtain a mixed solution, ultrasonically dispersing for at least 30 minutes, then adjusting the pH of the mixed solution to 9.5-10 with a 1-2M sodium hydroxide aqueous solution, continuing ultrasonically dispersing for at least 30 minutes, then adding sodium borohydride, wherein the mass ratio of the sodium borohydride to the silver nitrate is 1:10-15, and then stirring at a constant temperature of 90° C. for at least 4 hours. After the reaction is completed, centrifugation is performed using anhydrous ethanol and vacuum drying is performed to obtain silver-loaded modified carbon nanotubes, wherein the mass ratio of silver nitrate to the modified carbon nanotubes in the mixed solution is 5-9:1, the silver nitrate dispersion is a solution with a mass concentration of 25-30 g / L formed by uniformly dispersing silver nitrate in anhydrous ethanol, and the carbon nanotube dispersion is a solution with a mass concentration of 0.2-0.5 g / L formed by uniformly dispersing the modified carbon nanotubes in anhydrous ethanol;
[0013] (3) dispersing graphene oxide prepared by the Hummers method in deionized water to obtain a graphene dispersion, then adding KH550 hydrolyzate to the graphene dispersion, wherein the volume ratio of the graphene dispersion to the KH550 hydrolyzate is 2-3:500, reacting at 70-90° C. with constant temperature stirring for at least 4 hours, then filtering to obtain a solid product, washing the obtained solid product with water and vacuum drying to obtain KH550-modified graphene oxide, wherein the mass concentration of graphene oxide in the graphene dispersion is 0.1-0.2%, the KH550 hydrolyzate is a solution prepared by dissolving KH550 in deionized water and adjusting the pH value to 4.0 with acetic acid, and the mass concentration of KH550 in the KH560 hydrolyzate is 5.5-6.0 g / L;
[0014] (4) dispersing the KH550 modified graphene oxide obtained in step (3) in deionized water to obtain a dispersion, wherein the volume ratio of the KH550 modified graphene oxide to the deionized water is 1-2:200-260, then adding hydrazine hydrate to the dispersion, wherein the volume ratio of the hydrazine hydrate to the dispersion is 1-2:200, and then reducing the dispersion with stirring at 90° C. for at least 3 h. After the reduction is completed, the reaction solution is filtered, washed with deionized water, and vacuum dried to obtain KH550 modified reduced graphene oxide;
[0015] (5) adding a silver nitrate dispersion to a KH550 modified reduced graphene oxide dispersion to obtain a mixed solution, ultrasonically dispersing for at least 30 minutes, then adjusting the pH of the mixed solution to 9.5-10 with a 1-2M sodium hydroxide aqueous solution, continuing ultrasonically dispersing for at least 30 minutes, then adding 2-5g of sodium borohydride, and then stirring at 90°C for at least 4 hours. After the reaction is completed, centrifugally separating with anhydrous ethanol and vacuum drying to obtain silver-loaded KH550 modified reduced graphene oxide, wherein the mass ratio of silver nitrate to KH550 modified reduced graphene oxide in the mixed solution is 3-10:1, the silver nitrate dispersion is a solution with a mass concentration of 25-30g / L formed by uniformly dispersing silver nitrate in anhydrous ethanol, and the carbon nanotube dispersion is a solution with a mass concentration of 0.2-0.5g / L formed by uniformly dispersing KH550 modified reduced graphene oxide in anhydrous ethanol;
[0016] (6) 0.5-1 g of silver-loaded KH550 modified reduced graphene oxide and 1-2 g of silver-loaded modified carbon nanotubes are added to 200-250 mL of anhydrous ethanol and mixed evenly, and then 3-5 mL of triethylamine is added to the reaction system. Thereafter, the temperature of the reaction system is raised to 118-120° C., and the reaction is stirred at a constant temperature for at least 12 hours. During the stirring process, the amino group and the epoxy group in the reaction system undergo a ring-opening polymerization reaction. The reaction is monitored by FTIR. When the absorption peak of the hydroxyl group in the reaction system on the infrared spectrum no longer increases, the reaction is terminated, and the reaction liquid is filtered to obtain a solid product. The obtained solid product is washed with anhydrous ethanol until it is neutral, and then vacuum dried to obtain an antibacterial agent.
[0017] Preferably, the leveling agent includes one of BYK333, BYK3456, BYK3455, or a combination of two or more thereof.
[0018] Preferably, the defoamer is a silicone defoamer.
[0019] Preferably, the organosilicon defoaming agent includes one or a combination of two or more of trimethyl silicone oil, dimethyl polysiloxane or polysiloxane.
[0020] Preferably, the dispersant includes BYK-323, BYK-310, DISPERBYK-2163, DISPERBYK-2155 or BYK-9076 produced by BYK.
[0021] Preferably, the anti-settling agent comprises organic bentonite or polyamide wax.
[0022] The present invention has the following beneficial effects:
[0023] (1) The antibacterial agent obtained by the present invention is a product obtained by epoxy ring-opening reaction between amino groups on silver-loaded KH550-modified reduced graphene oxide and epoxy groups on silver-loaded modified carbon nanotubes. After the reaction is completed, a macromolecular structure of reduced graphene oxide and carbon nanotubes linked together by chemical bonds (ester groups) is obtained. The antibacterial agent has the antibacterial properties of both reduced graphene oxide and carbon nanotubes. In addition, silver nanoparticles with antibacterial effects are respectively loaded on the surfaces of reduced graphene oxide and carbon nanotubes, further improving the antibacterial properties of the photocurable coating obtained by the present invention.
[0024] (2) The present invention ingeniously realizes the compounding of the one-dimensional antibacterial agent and the two-dimensional antibacterial agent structure through the epoxy ring-opening reaction between the epoxy group and the amino group, constructs a more dense and complex antibacterial network in the photocurable coating system, and thus effectively improves the antibacterial performance of the obtained photocurable coating;
[0025] (3) The present invention chemically modifies carbon nanotubes by using KH570 and KH560 at the same time, and introduces abundant double bonds and epoxy groups. The epoxy groups are used for epoxy ring-opening reaction with amino groups, and the introduction of double bonds enables the obtained antibacterial agent to participate in the double bond polymerization reaction during the photocuring process, and introduces the structure of the composite antibacterial agent into the main resin structure of the photocurable paint film in the form of chemical bonds, which effectively avoids the problem of easy migration and precipitation of the antibacterial agent in the paint film, and significantly improves the antibacterial durability of the photocurable paint film. DETAILED DESCRIPTION
[0026] The present invention is described in detail below with reference to the examples. However, it should be understood that the following examples are only illustrative of the embodiments of the present invention, and are not intended to limit the scope of the present invention.
[0027] The hydroxylated carbon nanotubes used in the present invention are hydroxylated multi-walled carbon nanotubes purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd., with a diameter of 5-15 nm and model number 100236.
[0028] Example 1
[0029] A highly effective antibacterial light-curing coating, the composition of which is as follows in parts by weight:
[0030]
[0031] The epoxy acrylate includes Changxing UV epoxy oligomer 621A80.
[0032] The reactive diluent monomer includes propylene glycol diacrylate.
[0033] The photoinitiator includes photoinitiator 184 .
[0034] The preparation method of the antibacterial agent is as follows:
[0035] (1) adding hydroxylated carbon nanotubes and a silane coupling agent to an ethanol aqueous solution with a mass concentration of 95%, ultrasonically dispersing for 2 hours, and then isothermally reacting at 60° C. for 6 hours. After the reaction is completed, filtering to obtain a solid product, washing it with acetone for 3 times, and then vacuum drying it at 80° C. for 12 hours to obtain modified carbon nanotubes, wherein the mass ratio of the hydroxylated carbon nanotubes to the silane coupling agent is 1:1, and the silane coupling agent is composed of KH560 and KH570 in a mass ratio of 1:1; the mass concentration of the hydroxylated carbon nanotubes in the ethanol aqueous solution is 20 g / L;
[0036] (2) adding the silver nitrate dispersion to the modified carbon nanotube dispersion to obtain a mixed solution, ultrasonically dispersing for 30 minutes, then adjusting the pH of the mixed solution to 9.5 with a 1M sodium hydroxide aqueous solution, continuing ultrasonically dispersing for 30 minutes, then adding sodium borohydride, the mass ratio of the sodium borohydride to the silver nitrate being 1:10, and then stirring at a constant temperature of 90° C. for 4 hours. After the reaction is completed, centrifugation is performed using anhydrous ethanol and vacuum drying is performed to obtain silver-loaded modified carbon nanotubes, the mass ratio of silver nitrate to modified carbon nanotubes in the mixed solution being 5:1, the silver nitrate dispersion is a solution with a mass concentration of 25 g / L formed by uniformly dispersing silver nitrate in anhydrous ethanol, and the carbon nanotube dispersion is a solution with a mass concentration of 0.2 g / L formed by uniformly dispersing modified carbon nanotubes in anhydrous ethanol;
[0037] (3) dispersing graphene oxide prepared by the Hummers method in deionized water to obtain a graphene dispersion, then adding KH550 hydrolyzate to the graphene dispersion, wherein the volume ratio of the graphene dispersion to the KH550 hydrolyzate is 2:500, reacting at 70° C. with constant temperature stirring for 4 h, then filtering to obtain a solid product, washing the obtained solid product with water and vacuum drying to obtain KH550-modified graphene oxide, wherein the mass concentration of graphene oxide in the graphene dispersion is 0.1%, the KH550 hydrolyzate is a solution prepared by dissolving KH550 in deionized water and adjusting the pH value to 4.0 with acetic acid, and the mass concentration of KH550 in the KH560 hydrolyzate is 5.5 g / L;
[0038] (4) dispersing the KH550 modified graphene oxide obtained in step (3) in deionized water to obtain a mixed solution, wherein the volume ratio of the KH550 modified graphene oxide to the deionized water is 1:200, and then adding hydrazine hydrate to the mixed solution, wherein the volume ratio of the hydrazine hydrate to the mixed solution is 1:200, and then stirring at 90° C. for a reduction reaction for 3 h. After the reduction is completed, the reaction solution is filtered, washed with deionized water, and vacuum dried (60° C., 12 h) to obtain KH550 modified reduced graphene oxide;
[0039] (5) adding a silver nitrate dispersion to a KH550 modified reduced graphene oxide dispersion to obtain a mixed solution, ultrasonically dispersing for 30 minutes, and then adjusting the pH of the mixed solution to 9.5 with a 1M sodium hydroxide aqueous solution, continuing ultrasonic dispersion for 30 minutes, and then adding sodium borohydride, wherein the mass ratio of the sodium borohydride to the silver nitrate is 1:10, and then stirring at a constant temperature of 90° C. for 4 hours. After the reaction is completed, centrifugation is performed using anhydrous ethanol and vacuum drying is performed to obtain silver-loaded KH550 modified reduced graphene oxide, wherein the mass ratio of silver nitrate to KH550 modified reduced graphene oxide in the mixed solution is 3:1, the silver nitrate dispersion is a solution with a mass concentration of 25 g / L formed by uniformly dispersing silver nitrate in anhydrous ethanol, and the carbon nanotube dispersion is a solution with a mass concentration of 0.2 g / L formed by uniformly dispersing the KH550 modified reduced graphene oxide in anhydrous ethanol;
[0040] (6) 0.5 g of silver-loaded KH550-modified reduced graphene oxide and 1 g of silver-loaded modified carbon nanotubes were added to 200 mL of anhydrous ethanol and mixed evenly. Then, 3 mL of triethylamine was added to the reaction system. After that, the temperature of the reaction system was raised to 118°C and the reaction was stirred at a constant temperature for 12 h. During the stirring process, the amino group and the epoxy group in the reaction system underwent a ring-opening polymerization reaction. The reaction was monitored by FTIR. When the absorption peak of the hydroxyl group in the reaction system on the infrared spectrum no longer increased, the reaction was completed. The reaction solution was filtered to obtain a solid product. The obtained solid product was washed with anhydrous ethanol until neutral, and then vacuum dried (60°C, 12 h) to obtain an antibacterial agent.
[0041] The leveling agent is BYK333.
[0042] The organosilicon defoamer is trimethyl silicone oil.
[0043] The dispersant is BYK-323.
[0044] The anti-settling agent is polyamide wax.
[0045] Example 2
[0046] A highly effective antibacterial light-curing coating, the composition of which is as follows in parts by weight:
[0047]
[0048] The epoxy acrylate is Changxing UV epoxy oligomer 6210G.
[0049] The active diluent monomer is trimethylolpropane triacrylate.
[0050] The photoinitiator is photoinitiator 1173.
[0051] The preparation method of the antibacterial agent is as follows:
[0052] (1) adding hydroxylated carbon nanotubes and a silane coupling agent to an ethanol aqueous solution with a mass concentration of 95%, ultrasonically dispersing for 2 hours, and then isothermally reacting at 60° C. for 6 hours. After the reaction is completed, filtering to obtain a solid product, washing it with acetone for 3 times, and then vacuum drying it at 80° C. for 12 hours to obtain modified carbon nanotubes, wherein the mass ratio of the hydroxylated carbon nanotubes to the silane coupling agent is 1:1, and the silane coupling agent is composed of KH560 and KH570 in a mass ratio of 1:2; the mass concentration of the hydroxylated carbon nanotubes in the ethanol aqueous solution is 22 g / L;
[0053] (2) adding the silver nitrate dispersion to the modified carbon nanotube dispersion to obtain a mixed solution, ultrasonically dispersing for 30 minutes, then adjusting the pH of the mixed solution to 10 with a 1M sodium hydroxide aqueous solution, continuing ultrasonically dispersing for 30 minutes, then adding sodium borohydride, the mass ratio of the sodium borohydride to the silver nitrate being 1:12, and then stirring at a constant temperature of 90° C. for 4 hours. After the reaction is completed, centrifugation is performed using anhydrous ethanol and vacuum drying is performed to obtain silver-loaded modified carbon nanotubes, the mass ratio of silver nitrate to modified carbon nanotubes in the mixed solution being 7:1, the silver nitrate dispersion is a solution with a mass concentration of 25 g / L formed by uniformly dispersing silver nitrate in anhydrous ethanol, and the carbon nanotube dispersion is a solution with a mass concentration of 0.3 g / L formed by uniformly dispersing the modified carbon nanotubes in anhydrous ethanol;
[0054] (3) dispersing graphene oxide prepared by the Hummers method in deionized water to obtain a graphene dispersion, then adding KH550 hydrolyzate to the graphene dispersion, wherein the volume ratio of the graphene dispersion to the KH550 hydrolyzate is 3:500, reacting at 90° C. with constant temperature stirring for 4 h, then filtering to obtain a solid product, washing the obtained solid product with water and vacuum drying to obtain KH550-modified graphene oxide, wherein the mass concentration of graphene oxide in the graphene dispersion is 0.2%, the KH550 hydrolyzate is a solution prepared by dissolving KH550 in deionized water and adjusting the pH value to 4.0 with acetic acid, and the mass concentration of KH550 in the KH560 hydrolyzate is 6.0 g / L;
[0055] (4) dispersing the KH550 modified graphene oxide obtained in step (3) in deionized water to obtain a dispersion, wherein the volume ratio of the KH550 modified graphene oxide to the deionized water is 2:260, and then adding hydrazine hydrate to the dispersion, wherein the volume ratio of the hydrazine hydrate to the dispersion is 2:200, and then stirring at 90° C. for a reduction reaction for 3 h. After the reduction is completed, the reaction solution is filtered, washed with deionized water, and vacuum dried (60° C., 12 h) to obtain KH550 modified reduced graphene oxide;
[0056] (5) adding a silver nitrate dispersion to a KH550 modified reduced graphene oxide dispersion to obtain a mixed solution, ultrasonically dispersing for 30 minutes, then adjusting the pH of the mixed solution to 10 with a 2M sodium hydroxide aqueous solution, continuing ultrasonically dispersing for 30 minutes, then adding sodium borohydride, wherein the mass ratio of the sodium borohydride to the silver nitrate is 1:15, and then stirring at a constant temperature of 90° C. for 4 hours. After the reaction is completed, centrifugation is performed using anhydrous ethanol and vacuum drying is performed to obtain silver-loaded KH550 modified reduced graphene oxide, wherein the mass ratio of silver nitrate to KH550 modified reduced graphene oxide in the mixed solution is 8:1, the silver nitrate dispersion is a solution with a mass concentration of 30 g / L formed by uniformly dispersing silver nitrate in anhydrous ethanol, and the carbon nanotube dispersion is a solution with a mass concentration of 0.5 g / L formed by uniformly dispersing the KH550 modified reduced graphene oxide in anhydrous ethanol;
[0057] (6) 0.7 g of silver-loaded KH550-modified reduced graphene oxide and 1.5 g of silver-loaded modified carbon nanotubes were added to 230 mL of anhydrous ethanol and mixed evenly. Then, 4 mL of triethylamine was added to the reaction system. After that, the temperature of the reaction system was raised to 120°C and the reaction was stirred at a constant temperature for 12 h. During the stirring process, the amino group and the epoxy group in the reaction system underwent a ring-opening polymerization reaction. The reaction was monitored by FTIR. When the absorption peak of the hydroxyl group in the reaction system on the infrared spectrum no longer increased, the reaction was completed, and the reaction liquid was filtered to obtain a solid product. The obtained solid product was washed with anhydrous ethanol until neutral, and then vacuum dried (60°C, 12 h) to obtain an antibacterial agent.
[0058] The leveling agent is BYK3456.
[0059] The organosilicon defoamer is dimethyl polysiloxane.
[0060] The dispersant is BYK-310.
[0061] The anti-settling agent is organic bentonite.
[0062] Example 3
[0063] A highly effective antibacterial light-curing coating, the composition of which is as follows in parts by weight:
[0064]
[0065]
[0066] The epoxy acrylate is Changxing UV epoxy oligomer 6215-100.
[0067] The active diluent monomer is isobornyl acrylate.
[0068] The photoinitiator is photoinitiator TPO.
[0069] The preparation method of the antibacterial agent is as follows:
[0070] (1) adding hydroxylated carbon nanotubes and a silane coupling agent to an ethanol aqueous solution with a mass concentration of 95%, ultrasonically dispersing for 2 hours, and then isothermally reacting at 60° C. for 6 hours. After the reaction is completed, filtering to obtain a solid product, washing it with acetone for 3 times, and then vacuum drying it at 80° C. for 12 hours to obtain modified carbon nanotubes, wherein the mass ratio of the hydroxylated carbon nanotubes to the silane coupling agent is 1:1, and the silane coupling agent is composed of KH560 and KH570 in a mass ratio of 2:3; the mass concentration of the hydroxylated carbon nanotubes in the ethanol aqueous solution is 25 g / L;
[0071] (2) adding the silver nitrate dispersion to the modified carbon nanotube dispersion to obtain a mixed solution, ultrasonically dispersing for 30 minutes, then adjusting the pH of the mixed solution to 9.5 with a 2M sodium hydroxide aqueous solution, continuing ultrasonically dispersing for 30 minutes, then adding sodium borohydride, the mass ratio of the sodium borohydride to the silver nitrate being 1:15, and then stirring at a constant temperature of 90° C. for 4 hours. After the reaction is completed, centrifugation is performed using anhydrous ethanol and vacuum drying is performed to obtain silver-loaded modified carbon nanotubes, the mass ratio of silver nitrate to modified carbon nanotubes in the mixed solution being 9:1, the silver nitrate dispersion is a solution with a mass concentration of 30 g / L formed by uniformly dispersing silver nitrate in anhydrous ethanol, and the carbon nanotube dispersion is a solution with a mass concentration of 0.5 g / L formed by uniformly dispersing the modified carbon nanotubes in anhydrous ethanol;
[0072] (3) dispersing graphene oxide prepared by the Hummers method in deionized water to obtain a graphene dispersion, then adding KH550 hydrolyzate to the graphene dispersion, wherein the volume ratio of the graphene dispersion to the KH550 hydrolyzate is 3:500, reacting at 90° C. with constant temperature stirring for 4 h, then filtering to obtain a solid product, washing the obtained solid product with water and vacuum drying to obtain KH550-modified graphene oxide, wherein the mass concentration of graphene oxide in the graphene dispersion is 0.2%, the KH550 hydrolyzate is a solution prepared by dissolving KH550 in deionized water and adjusting the pH value to 4.0 with acetic acid, and the mass concentration of KH550 in the KH560 hydrolyzate is 6.0 g / L;
[0073] (4) dispersing the KH550 modified graphene oxide obtained in step (3) in deionized water to obtain a dispersion, wherein the volume ratio of the KH550 modified graphene oxide to the deionized water is 1:200, and then adding hydrazine hydrate to the dispersion, wherein the volume ratio of the hydrazine hydrate to the dispersion is 2:200, and then stirring at 90° C. for a reduction reaction for 3 h. After the reduction is completed, the reaction solution is filtered, washed with deionized water, and vacuum dried (60° C., 12 h) to obtain KH550 modified reduced graphene oxide;
[0074] (5) adding a silver nitrate dispersion to a KH550 modified reduced graphene oxide dispersion to obtain a mixed solution, ultrasonically dispersing for 30 minutes, and then adjusting the pH of the mixed solution to 10 using a 2M sodium hydroxide aqueous solution, continuing ultrasonic dispersion for 30 minutes, and then adding sodium borohydride, wherein the mass ratio of the sodium borohydride to the silver nitrate is 1:13, and then stirring at a constant temperature of 90° C. for 4 hours. After the reaction is completed, centrifugation is performed using anhydrous ethanol and vacuum drying is performed to obtain silver-loaded KH550 modified reduced graphene oxide, wherein the mass ratio of silver nitrate to KH550 modified reduced graphene oxide in the mixed solution is 10:1, the silver nitrate dispersion is a solution having a mass concentration of 28 g / L formed by uniformly dispersing silver nitrate in anhydrous ethanol, and the carbon nanotube dispersion is a solution having a mass concentration of 0.4 g / L formed by uniformly dispersing the KH550 modified reduced graphene oxide in anhydrous ethanol;
[0075] (6) 1 g of silver-loaded KH550-modified reduced graphene oxide and 2 g of silver-loaded modified carbon nanotubes were added to 250 mL of anhydrous ethanol and mixed evenly. Then, 5 mL of triethylamine was added to the reaction system. After that, the temperature of the reaction system was raised to 120°C and the reaction was stirred at a constant temperature for 12 h. During the stirring process, the amino group and the epoxy group in the reaction system underwent a ring-opening polymerization reaction. The reaction was monitored by FTIR. When the absorption peak of the hydroxyl group in the reaction system on the infrared spectrum no longer increased, the reaction was terminated. The reaction solution was filtered to obtain a solid product. The obtained solid product was washed with anhydrous ethanol until neutral, and then vacuum dried (60°C, 12 h) to obtain an antibacterial agent.
[0076] The leveling agent is BYK3455.
[0077] The organosilicon defoamer is polysiloxane.
[0078] The dispersant is BYK-9076.
[0079] The anti-settling agent is organic bentonite.
[0080] Example 4 is the same as Example 1, except that the active diluent monomer in Example 4 is composed of propylene glycol diacrylate and trimethylolpropane triacrylate in a mass ratio of 2:1.
[0081] Example 5 is the same as Example 1, except that the active diluent monomer in Example 5 is composed of propylene glycol diacrylate and trimethylolpropane triacrylate in a mass ratio of 1:2.
[0082] Example 6 is the same as Example 1, except that the active diluent monomer in Example 6 is composed of propylene glycol diacrylate and isobornyl acrylate in a mass ratio of 1:1.
[0083] Example 7 is the same as Example 1, except that the active diluent monomer in Example 7 is composed of trimethylolpropane triacrylate and isobornyl acrylate in a mass ratio of 1:1.
[0084] Comparative Example 1 is the same as Example 1, except that the antibacterial agent in Comparative Example 1 is silver-loaded KH550 modified reduced graphene oxide.
[0085] Comparative Example 2 is the same as Example 1, except that the antibacterial agent in Comparative Example 2 is silver-loaded modified carbon nanotubes.
[0086] Comparative Example 3 is the same as Example 1, except that step (4) does not exist in the preparation process of the antibacterial agent in Comparative Example 3, and the KH550-modified reduced graphene oxide in step (5) is replaced by KH550-modified graphene oxide.
[0087] Comparative Example 4 is the same as Example 1, except that the antibacterial agent in Comparative Example 4 is a mixture of the silver-loaded KH550 modified reduced graphene oxide and the silver-loaded modified carbon nanotubes in Example 1 in a mass ratio of 1:2.
[0088] Performance Testing
[0089] The antibacterial coatings obtained in the examples of the present invention and the comparative examples were subjected to relevant performance tests, and the specific test results are shown in Table 1.
[0090] Adhesion: ASTM D3359-2002 (100-grid test).
[0091] Hardness: ASTM D3363, Chinese pencil.
[0092] Antibacterial property: quantitatively inoculate bacteria on the sample to be tested, use the film method to make the bacteria evenly contact the sample, detect the number of live bacteria in the sample after a certain period of cultivation, and calculate the antibacterial rate of the sample. According to the requirements of the standard "HG3950-2007 Antibacterial Wood Paint", the antibacterial properties of the coatings obtained in the examples of the present invention and the comparative examples were tested respectively.
[0093] Table 1
[0094]
[0095] Based on the above ideal embodiments of the present invention, the relevant staff can make various changes and modifications without departing from the technical concept of the present invention through the above description. The technical scope of the present invention is not limited to the contents of the specification, and its technical scope must be determined according to the scope of the claims.
Claims
1. A highly efficient antibacterial light-curing coating, characterized in that: The composition includes the following components by weight:
2. A highly efficient antibacterial light-curing coating according to claim 1, characterized in that: The epoxy acrylate includes one or a combination of two or more of Changxing UV epoxy oligomers 6215-100, 621A80, 6210G, 6233, and 623A80.
3. The high-efficiency antibacterial light-curing coating according to claim 1, characterized in that: The active diluent monomer includes one or a combination of two or more of propylene glycol diacrylate, trimethylolpropane triacrylate or isobornyl acrylate.
4. The high-efficiency antibacterial light-curing coating according to claim 1, characterized in that: The photoinitiator includes one of photoinitiator 184, photoinitiator 1173, photoinitiator TPO, photoinitiator 819, or a combination of two or more thereof.
5. The high-efficiency antibacterial light-curing coating according to claim 1, characterized in that: The preparation method of the antibacterial agent comprises the following steps: (1) adding hydroxylated carbon nanotubes and a silane coupling agent to an ethanol aqueous solution with a mass concentration of 95%, ultrasonically dispersing for at least 2 hours, and then isothermally reacting at 60° C. for at least 6 hours. After the reaction is completed, filtering to obtain a solid product, washing with acetone at least 3 times, and then vacuum drying at 80° C. for at least 12 hours to obtain modified carbon nanotubes, wherein the mass ratio of the hydroxylated carbon nanotubes to the silane coupling agent is 1:1, and the silane coupling agent is composed of KH560 and KH570 in a mass ratio of 1-3:1-3; the mass concentration of the hydroxylated carbon nanotubes in the ethanol aqueous solution is 20-25 g / L; (2) adding the silver nitrate dispersion to the modified carbon nanotube dispersion to obtain a mixed solution, ultrasonically dispersing for at least 30 minutes, then adjusting the pH of the mixed solution to 9.5-10 with a 1-2M sodium hydroxide aqueous solution, continuing ultrasonically dispersing for at least 30 minutes, then adding sodium borohydride, wherein the mass ratio of the sodium borohydride to the silver nitrate is 1:10-15, and then stirring at a constant temperature of 90° C. for at least 4 hours. After the reaction is completed, centrifugation is performed using anhydrous ethanol and vacuum drying is performed to obtain silver-loaded modified carbon nanotubes, wherein the mass ratio of silver nitrate to the modified carbon nanotubes in the mixed solution is 5-9:1, the silver nitrate dispersion is a solution with a mass concentration of 25-30 g / L formed by uniformly dispersing silver nitrate in anhydrous ethanol, and the carbon nanotube dispersion is a solution with a mass concentration of 0.2-0.5 g / L formed by uniformly dispersing the modified carbon nanotubes in anhydrous ethanol; (3) dispersing graphene oxide prepared by the Hummers method in deionized water to obtain a graphene dispersion, then adding KH550 hydrolyzate to the graphene dispersion, wherein the volume ratio of the graphene dispersion to the KH550 hydrolyzate is 2-3:500, reacting at 70-90° C. with constant temperature stirring for at least 4 hours, then filtering to obtain a solid product, washing the obtained solid product with water and vacuum drying to obtain KH550-modified graphene oxide, wherein the mass concentration of graphene oxide in the graphene dispersion is 0.1-0.2%, the KH550 hydrolyzate is a solution prepared by dissolving KH550 in deionized water and adjusting the pH value to 4.0 with acetic acid, and the mass concentration of KH550 in the KH560 hydrolyzate is 5.5-6.0 g / L; (4) dispersing the KH550 modified graphene oxide obtained in step (3) in deionized water to obtain a dispersion, wherein the volume ratio of the KH550 modified graphene oxide to the deionized water is 1-2:200-260, then adding hydrazine hydrate to the dispersion, wherein the volume ratio of the hydrazine hydrate to the dispersion is 1-2:200, and then reducing the dispersion with stirring at 90° C. for at least 3 h. After the reduction is completed, the reaction solution is filtered, washed with deionized water, and vacuum dried to obtain KH550 modified reduced graphene oxide; (5) adding a silver nitrate dispersion to a KH550 modified reduced graphene oxide dispersion to obtain a mixed solution, ultrasonically dispersing for at least 30 minutes, then adjusting the pH of the mixed solution to 9.5-10 with a 1-2M sodium hydroxide aqueous solution, continuing ultrasonically dispersing for at least 30 minutes, then adding 2-5g of sodium borohydride, and then stirring at 90°C for at least 4 hours. After the reaction is completed, centrifugally separating with anhydrous ethanol and vacuum drying to obtain silver-loaded KH550 modified reduced graphene oxide, wherein the mass ratio of silver nitrate to KH550 modified reduced graphene oxide in the mixed solution is 3-10:1, the silver nitrate dispersion is a solution with a mass concentration of 25-30g / L formed by uniformly dispersing silver nitrate in anhydrous ethanol, and the carbon nanotube dispersion is a solution with a mass concentration of 0.2-0.5g / L formed by uniformly dispersing KH550 modified reduced graphene oxide in anhydrous ethanol; (6) 0.5-1 g of silver-loaded KH550 modified reduced graphene oxide and 1-2 g of silver-loaded modified carbon nanotubes are added to 200-250 mL of anhydrous ethanol and mixed evenly, and then 3-5 mL of triethylamine is added to the reaction system. Thereafter, the temperature of the reaction system is raised to 118-120° C., and the reaction is stirred at a constant temperature for at least 12 hours. During the stirring process, the amino group and the epoxy group in the reaction system undergo a ring-opening polymerization reaction. The reaction is monitored by FTIR. When the absorption peak of the hydroxyl group in the reaction system on the infrared spectrum no longer increases, the reaction is terminated, and the reaction liquid is filtered to obtain a solid product. The obtained solid product is washed with anhydrous ethanol until it is neutral, and then vacuum dried to obtain an antibacterial agent.
6. The high-efficiency antibacterial light-curing coating according to claim 1, characterized in that: The leveling agent includes one of BYK333, BYK3456, BYK3455, or a combination of two or more thereof.
7. The high-efficiency antibacterial light-curing coating according to claim 1, characterized in that: The defoamer is an organosilicon defoamer.
8. The high-efficiency antibacterial light-curing coating according to claim 7, characterized in that: The organosilicon defoamer comprises one or a combination of two or more of trimethyl silicone oil, dimethyl polysiloxane or polysiloxane.
9. The high-efficiency antibacterial light-curing coating according to claim 1, characterized in that: The dispersant includes BYK-323, BYK-310, DISPERBYK-2163, DISPERBYK-2155 or BYK-9076 produced by BYK.
10. The high-efficiency antibacterial light-curing coating according to claim 1, characterized in that: The anti-settling agent includes organic bentonite or polyamide wax.